Post-traumatic knee osteoarthritis in the young patient: therapeutic dilemmas and emerging technologies - Stiebel M; Miller LE; Block JE (Dove Medical Press, 2014)
Matthew Stiebel,1 Larry E Miller,2,3 Jon E Block3 1Palm Beach Sports Medicine, West Palm Beach, FL, USA; 2Miller Scientific Consulting, Inc, Asheville, NC, USA; 3The Jon Block Group, San Francisco, CA, USA Abstract: Traumatic knee injury is common in young adults and strongly contributes to premature development of knee osteoarthritis (OA). Post-traumatic knee OA poses a therapeutic dilemma to the physician, since no known therapy has an acceptable safety profile, effectively relieves joint pain, and enjoys reasonable patient acceptance. Consequently, these young patients will ultimately be faced with the decision to either undergo surgical intervention, despite prosthesis durability concerns, or to continue with ineffective nonsurgical treatment. Emerging therapies, such as biologics, disease-modifying drugs, partial joint resurfacings, and minimally invasive joint-unloading implants are currently being studied to fill this therapeutic void in the young patient with post-traumatic knee OA. Keywords: injury, knee, osteoarthritis, post-traumatic, implant, joint unloading, KineSpring, minimally invasive